Switch on-switch off small-scale mining: Environmental performance in a life cycle perspective. (20th August 2021) - Beylot, Antoine; Muller, Stéphanie; Segura-Salazar, Juliana; Brito-Parada, Pablo; Paneri, Anshul; Yan, Xiaoyu; Lai, Frédéric; Roethe, Richard; Thomas, Gareth; Goettmann, Frédéric; Braun, Marius; Moradi, Saeid; et al.
Abstract: A switch on-switch off (SOSO) approach to mining relies on an integrated modular and mobile plant. It is appropriate for rapid start-up and cessation of production from ore deposits that have economic viability dependent on fluctuating commodity prices. This study aims at assessing the environmental performance of the SOSO approach in a life cycle perspective, using evidence collected during its pilot-scale implementation on a high-grade lead deposit located in Bosnia-Herzegovina. The deployed modules include: i) a selective mining tool, ii) a comminution module with crusher and screen, and iii) a gravity separation module with screen, spirals and a shaking table. The Life Cycle Inventory is based on a comprehensive and transparent set of data, drawn from the on-site pilot tests, completed with additional calculations (including process simulation with USIM-PAC®), scenarios (regarding energy), and some generic data and assumptions. The potential environmental impacts are calculated considering 13 impact categories of the EF 2.0 impact assessment method. The production of one tonne of Pb concentrate, with a Pb-content of 58.7%, induces in particular the potential generation of 897 kg CO2 -eq. Moreover, the contribution analysis enables identification of the environmental hotspots, including the consumption of electricity supplied by on-site diesel generators that contributes to more than 90% of the total impacts in seven impact categories. Finally, this article discusses i) how advantageous the SOSO approach is compared to large-scale lead mining regarding some of its associated key environmental hotspots, ii) the potential for reduction of the impacts associated with electricity consumption, in particular through the implementation of a renewable electricity supply mix (solar photovoltaics and biomass-based), iii) the contributions of equipment and tailings to the total impacts, and iv) the contribution of the SOSO approach to resource accessibility and depletion. The inclusion of data outputs of mineral processing simulation in LCA appears a promising development towards optimization of the SOSO modular process chain, based on life-cycle environmental criteria and accounting for the site-dependent variability of ores and processes. Highlights: The environmental performance of switch on-switch off (SOSO) mining is assessed. Contributions of extraction activities to key impacts reveals space for improvement. SOSO approach increases the potential to make use of the value of metals in ground. Advantages of SOSO approach are increased by suitable electricity demand and supply . Toxicity and ecotoxicity impacts are influenced by equipment and tailings management.